Implementation of the AIDA Method in Designing the Company Profile Website of the PT Bhaskara Puspa Alam - Robinson, Vincent Tio; Perangin-Angin, Johanes Terang Kita; Hoki, Leony (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
A company profile is an image of a company’s professionalism that can be used as an effective marketing tool because it contains visual elements in the form of images and text, especially if other multimedia elements are added, it will make the company profile design look more attractive and can make customers interested in the products offered. The role of a company profile is very influential in the development and existence of goods or services from a company that is starting to develop, where a company profile is a company profile that is a general description of a company that wants to carry out a series of promotional activities through a video, book, website or other media. PT. Bhaskara Puspa Alami is a company engaged in the building materials sector, namely cement. This company is still not widely known to the wider community because it has not done much promotion through digital technology. To introduce it widely to the public, it is necessary to design a company profile website for PT. Bhaskara Puspa Alam. In this research, the AIDA method will be used to promote the campus. The AIDA model is a decision-making process consisting of attention, interest, desire, and finally the action of the decision (action) [5]. First, Attention means that the advertisement must be able to attract the attention of the target audience. Second, Interest, where the advertisement deals with how consumers are interested and have further desires. Third, Desire means that the advertisement must be able to move people’s desire to own or enjoy the product. Then, Action means that the advertisement must have the "power" to persuade potential buyers to immediately make a purchase.